2003
DOI: 10.1093/geront/43.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and Retention of Older Minorities in Mental Health Services Research

Abstract: Although these data are observational, and rigorous research on the best methods for recruiting and retaining older minorities is still necessary, the results suggest that a consumer-centered model of research yields greater overall recruitment and retention rates than do traditional research methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 140 publications
(157 citation statements)
references
References 19 publications
6
151
0
Order By: Relevance
“…Although heterogeneity of studies and populations renders definitive comparisons difficult, the poor showing of community outreach merits further exploration as this is a commonly proposed intervention. 3,7,9,10,22,72 It is important to note that community outreach likely has the advantage of being the recruitment strategy that may alleviate distrust. 3,6 Our finding that outreach rarely was the most effective independent strategy may stem from the individual studies/populations in our review.…”
Section: Resultsmentioning
confidence: 99%
“…Although heterogeneity of studies and populations renders definitive comparisons difficult, the poor showing of community outreach merits further exploration as this is a commonly proposed intervention. 3,7,9,10,22,72 It is important to note that community outreach likely has the advantage of being the recruitment strategy that may alleviate distrust. 3,6 Our finding that outreach rarely was the most effective independent strategy may stem from the individual studies/populations in our review.…”
Section: Resultsmentioning
confidence: 99%
“…The few studies addressing retention issues highlighted the importance of having the same interviewers or field staff over time; having staff from the targeted community; providing social support; and having accessible locations for intervention implementation and/or data collection, regular telephone reminders, and timely incentive payments (7,9,40,49,83,89,120). DilworthAnderson and colleagues (32) point out the importance of the interviewers' knowledge of family dynamics and providing a toll-free phone number to participants to increase accessibility of project staff.…”
Section: Retentionmentioning
confidence: 99%
“…Some studies have found success in matching recruiters with the race/ethnicity of participants 90 or utilizing a community member as a recruiter 91 Others have found recruiter experience and/or training recruiters to be more important than ethnic matching. 91 A potential participant's ethnic identity is likely an important mediating factor in whether race/ ethnicity-matched recruitment will be effective. 92 Cultural targeting is also relevant to intervention implementation, discussed below.…”
Section: Recruitmentmentioning
confidence: 99%